Bounce Behaviour of Kantowski-Sach Cosmological Model in General Relativity (Global Journal of Science Frontier Research, 2017)
Kantowski-Sach cosmological model has obtained in the general theory of relativity. The source for energy-momentum tensor is assumed a perfect fluid. The field equations have solved by using special form of the average scale factor
Keywords: kantowski-sach space-time; bouncing universe